Analisis Kepemimpinan Kepala Sekolah Dan Lingkungan Kerja Terhadap Kinerja Guru Tingkat SMK - Dewi Wahyuni; Rani Rahim; Nur Hayati (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
The purpose of this study is to analyze: (1) find out how the influence of the principal's leadership on the performance of vocational level teachers. (2) knowing how the influence of the work environment on the performance of teachers at the SMK level. (3) To find out how the influence of school principal leadership and work environment on the performance of vocational school teachers. This research is a quantitative study according to Sujawerni. Randomly, five schools were selected as research subjects, namely Medan Darussalam Vocational School, Setiabudi Vocational School, Galang Insan Mandiri Vocational School, Medan 3 Vocational School and Medan 5 Vocational School. The analysis test results show that: (1) the performance of SMK Darussalam teachers is influenced by the leadership of the school principal and work environment by 0.157 (15.7%) while 84.3% is influenced by other variables. (2) The performance of SMK Setiabudi teachers is influenced by the leadership of the school principal and work environment by 0.536 (53.6%) while 46.4% is influenced by other variables. (3) The performance of Galang Insan Mandiri SMKS teachers was influenced by the leadership of the school principal and work environment by 0.376 (37.6%) while 62.4% was influenced by other variables. (4) The performance of SMK Negeri 3 Medan teachers is influenced by the leadership of the school principal and work environment by 0.555 (55.5%) while 44.5% is influenced by other variables. (5) The performance of SMK Negeri 5 Medan teachers is influenced by the leadership of the school principal and work environment by 0.138 (13.8%) while 86.2% is influenced by other variables.